Weight loss patterns in decomposing litter of Coriaria nepalensis, an actinorhizal shrub from degraded land - BARGALI, KIRAN; MANRAL, VIJYETA; BARGALI, S S (The Indian Journal of Agricultural Sciences, 2015)
The present study deals with litter decomposition patterns in different components of Coriaria nepalensis Wall. Mature freshly-fallen leaves, twigs, roots and nodules of C. nepalensis were collected. The litter bag technique was used to assess weight loss and decay rate. Litter bags containing 5 g litter were placed under the canopy of C. nepalensis. Three litterbags per component were collected at monthly interval, brought to the laboratory, dried and weighed. Nodules decomposed very fast (63.9%) within 30 days followed by leaves (57.6% within 30 days) while decomposition of root was relatively slow, i.e. 53.2% within 210 days. The percent of material loss was 95.2% for nodule, 87.8% for leaves, 85.6% for inflorescence, 82.0% for twigs and 53.2% for root for entire duration. Decomposition rate coefficient (k) significantly ranged from 0.025/day (roots) to 0.101/day (nodules). The percent weight remaining was significantly affected by days elapsed, soil temperature and soil moisture.